Cryogenic III-V and Nb electronics integrated on silicon for large-scale quantum computing platforms - Jaeyong Jeong; Seong Kwang Kim; Yoon-Je Suh; Jisung Lee; Joonyoung Choi; Joon Pyo Kim; Bong Ho Kim; Juhyuk Park; Joonsup Shim; Nahyun Rheem; Chan Jik Lee; Younjung Jo; et al. (Nature Communications)
Abstract Quantum computers now encounter the significant challenge of scalability, similar to the issue that classical computing faced previously. Recent results in high-fidelity spin qubits manufactured with a Si CMOS technology, along with demonstrations that cryogenic CMOS-based control/readout electronics can be integrated into the same chip or die, opens up an opportunity to break out the challenges of qubit size, I/O, and integrability. However, the power consumption of cryogenic CMOS-based control/readout electronics cannot support thousands or millions of qubits. Here, we show that III–V two-dimensional electron gas and Nb superconductor-based cryogenic electronics can be integrated with Si and operate at extremely low power levels, enabling the control and readout for millions of qubits. Our devices offer a unity gain cutoff frequency of 601 GHz, a unity power gain cutoff frequency of 593 GHz, and a low noise indication factor $$\left(\sqrt{I_{{{\rm{D}}}}}\, {g}_{{{{\rm{m}}}}}^{-1}\right)$$ I D g m − 1 of $$0.21\sqrt{{{{\rm{Vmm}}}}}\scriptstyle\sqrt{S^{-1}}$$ 0.21 Vmm S − 1 at 4 K using more than 10 times less power consumption than CMOS.